Bibliografía contemporánea costarricense sobre historia de Costa Rica, Centroamérica y Panamá 1990-1995 - Taracena Arriola, Luis Pedro (1997)
Bibliographic investigation about the Works on the history of Centroamerica  published en Costa Rica between 1990 and 1995.